Arctic Storm Surge and Tidal Experiment - Matthews, J B; McGregor, R (1972)
ARPA has sponsored an on-going project to operate two tide gauges simultaneously on the Arctic coast of Alaska for one year. The project operated one gauge at Point Barrow throughout the contract period and under a no-cost 6- month extension of the contract operated a gauge at Oliktok Point. The original objectives of the experiment; to obtain simultaneous tide gauge data for the arctic Alaskan coast were therefore fulfilled. A test of a bourdon tube 'Filloux' type gauge was made at Point Barrow simultaneously with 'Bubbler' gauge measurements. The original raw data were reduced to computer compatible form, plotted, checked and corrected. The corrected data are now stored on tape for further evaluation.